2020
DOI: 10.1002/adom.201901647
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Wing Inspired High Performance Infrared Detection with Spectral Selectivity

Abstract: This work explores an alternative infrared (IR) detection mechanism that is based on the desorption of vapor molecules from the Morpho butterfly nanostructures under the stimulation of incoming IR photons, and demonstrates the use of such stimulated desorption for both broadband and wavelength selective IR detection. Compared to the structural deformation‐based IR detection using the Morpho nanostructures, this detection mechanism enables more than an order of magnitude of improvement in both the response of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…By tailoring these scale morphologies, butterflies produce unique visual appearances ( 4 7 ), ensure thermal regulation ( 8 ) and water repellency ( 9 ), or generate beneficial acoustic ( 10 ) and aerodynamic effects ( 11 ). Interdisciplinary interest in these material functionalities has led to scientific advances in the comprehensive assessment of the scales’ multifunctional material properties ( 12 ), design of next-generation bioinspired functional materials ( 13 , 14 ), identification of key genes in patterning and structural color ( 15 19 ), and evaluation of the impact of ecological factors on biodiversity ( 20 , 21 ). Although the enviable functionality of butterfly wings depends heavily on the precise structural architecture of the wing scales, little is known about the dynamics, processes, and phenomena involved in scale development ( 22 ).…”
mentioning
confidence: 99%
“…By tailoring these scale morphologies, butterflies produce unique visual appearances ( 4 7 ), ensure thermal regulation ( 8 ) and water repellency ( 9 ), or generate beneficial acoustic ( 10 ) and aerodynamic effects ( 11 ). Interdisciplinary interest in these material functionalities has led to scientific advances in the comprehensive assessment of the scales’ multifunctional material properties ( 12 ), design of next-generation bioinspired functional materials ( 13 , 14 ), identification of key genes in patterning and structural color ( 15 19 ), and evaluation of the impact of ecological factors on biodiversity ( 20 , 21 ). Although the enviable functionality of butterfly wings depends heavily on the precise structural architecture of the wing scales, little is known about the dynamics, processes, and phenomena involved in scale development ( 22 ).…”
mentioning
confidence: 99%
“…In the meanwhile, this team also found that vapor molecules such as water could be adsorbed on the wing scales and the IR radiation could induce the desorption of vapor molecules (Figure 21e). 232 Such IR-responsive desorption of vapor molecules could also change the reflectivity of the butterfly wings. Under this working principle, the temperature sensitivity of IR detectors was further improved to 4 mK.…”
Section: Bioinspired Ir Detectionmentioning
confidence: 99%
“…For instance, banded demoiselles, jewel beetles, gold beetles, blue morpho butterflies, Madagascan sunset moths, and orchid bees have brought forward a wide variety of photonic structures to reflect incident light. 31,32 Body colorations allow the insects to provide camouflage against predators on the hunt, warn predators of toxicity, increase visibility to potential mates, or create a dynamic form of information. Some specific cephalopods, as the most intelligent invertebrate, can even tune structural colors across the entire visible spectrum without the loss of color fidelity.…”
Section: T H Imentioning
confidence: 99%
“…Over more than 400 million years of natural selection, living organisms have evolved diverse features and favorable lifestyles to adapt to their current environments. For instance, banded demoiselles, jewel beetles, gold beetles, blue morpho butterflies, Madagascan sunset moths, and orchid bees have brought forward a wide variety of photonic structures to reflect incident light. , Body colorations allow the insects to provide camouflage against predators on the hunt, warn predators of toxicity, increase visibility to potential mates, or create a dynamic form of information. Some specific cephalopods, as the most intelligent invertebrate, can even tune structural colors across the entire visible spectrum without the loss of color fidelity. The adaptive coloration is enabled by modulating the geometry and extracellular spacing of Bragg stack hollow architectures within dermal iridophores in their soft and fixable skins.…”
Section: Introductionmentioning
confidence: 99%